2008
DOI: 10.1094/phyto-98-5-0529
|View full text |Cite
|
Sign up to set email alerts
|

Oidium neolycopersici: Intraspecific Variability Inferred from Amplified Fragment Length Polymorphism Analysis and Relationship with Closely Related Powdery Mildew Fungi Infecting Various Plant Species

Abstract: Jankovics, T., Bai, Y., Kovács, G. M., Bardin, M., Nicot, P. C., Toyoda, H., Matsuda, Y., Niks, R. E., and Kiss, L. 2008. Oidium neolycopersici: Intraspecific variability inferred from amplified fragment length polymorphism analysis and relationship with closely related powdery mildew fungi infecting various plant species. Phytopathology 98:529-540.Previous works indicated a considerable variation in the pathogenicity, virulence, and host range of Oidium neolycopersici isolates causing tomato powdery mildew ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…Study of intraspecific variability of 10 Oidium neolycopersici isolates originating from various countries of Europe, North America and Japan showed that ITS sequences were identical for all 10 isolates, however AFLP analysis discovered a high level of diversity in the isolates and they were represented by different genotypes (Jankovics et al 2008). The reason why isolates were identical based on ITS, but very different based on AFLP fingerprinting, might be due to the fact that PM genomes are largely occupied by repetitive sequences (Spanu 2012), thus many differences could be detected by AFLP in those regions.…”
Section: Intraspecific Variability Of O Neolycopersicimentioning
confidence: 98%
See 1 more Smart Citation
“…Study of intraspecific variability of 10 Oidium neolycopersici isolates originating from various countries of Europe, North America and Japan showed that ITS sequences were identical for all 10 isolates, however AFLP analysis discovered a high level of diversity in the isolates and they were represented by different genotypes (Jankovics et al 2008). The reason why isolates were identical based on ITS, but very different based on AFLP fingerprinting, might be due to the fact that PM genomes are largely occupied by repetitive sequences (Spanu 2012), thus many differences could be detected by AFLP in those regions.…”
Section: Intraspecific Variability Of O Neolycopersicimentioning
confidence: 98%
“…The same study also compared anamorphs of O. neolycopersici and powdery mildews from host plants Aquilegia vulgaris, Chelidonium majus, Passiflora caerulea and Sedum alboroseum, but anamorphs of these species could not be distinguished morphologically, and they were phylogenetically very close to O. neolycopersici. All those species (anamorphs) of powdery mildew were virulent only on their original host species, except O. neolycopersici, which was able to infect S. alboroseum, tobacco, petunia and Arabidopsis thalliana (Jankovics et al 2008).…”
Section: Intraspecific Variability Of O Neolycopersicimentioning
confidence: 99%
“…The nucleotide sequences obtained were deposited at the (Jankovics et al, 2008;Kashimoto et al, 2003;Seifi et al, 2012), and therefore both isolates belonged to the clade O. neolycopersici. Based on these results, we assigned O.…”
Section: Discussionmentioning
confidence: 99%
“…Now it is believed that O. neolycopersici is present worldwide, except in Australia where O. lycopersici is the causal agent for PM disease in tomato (Kiss et al 2001(Kiss et al , 2005. Although there is not a consensus on the host range of O. neolycopersici Lebeda et al 2013), there is some evidence suggesting that this pathogen is adapted to plant species from 13 plant families (Whipps et al 1998;Jankovics et al 2008). For further information of O. lycopersici and O. neolycopersici, please see the comprehensive review by Lebeda et al (2013).…”
Section: Oidium Lycopersici and O Neolycopersicimentioning
confidence: 99%